2017
DOI: 10.3788/col201715.051401
|View full text |Cite
|
Sign up to set email alerts
|

Laser-accelerated self-assembly of colloidal particles at the water–air interface

Abstract: We experimentally demonstrate that optical tweezers can be used to accelerate the self-assembly of colloidal particles at a water-air interface in this Letter. The thermal flow induced by optical tweezers dominates the growth acceleration at the interface. Furthermore, optical tweezers are used to create a local growth peak at the growing front, which is used to study the preferential incorporation positions of incoming particles. The results show that the particles surfed with a strong Marangoni flow tend to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Optical confinement, a noncontact technique widely applied in various disciplines of science and technology (i.e., physics, chemistry, and biology like single molecule biophysics and cell biology ), is advantageous for trapping and manipulating objects such as organelles inside cells, colloidal particles, and nanoparticles. When laser light is illuminated on an interface, it generates a local hotspot that induces convection currents, which assist in the aggregation of microparticles. This confinement technique facilitates the creation and manipulation of assemblies of nano- and microcolloidal particles and is thus employed in analyzing the characteristics of various interfacial systems, like liquid–solid, liquid–liquid, and air–liquid . The properties of such assemblies are vastly different from their constituent particles, because of which the phenomena can alter the interfacial properties in different systems …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Optical confinement, a noncontact technique widely applied in various disciplines of science and technology (i.e., physics, chemistry, and biology like single molecule biophysics and cell biology ), is advantageous for trapping and manipulating objects such as organelles inside cells, colloidal particles, and nanoparticles. When laser light is illuminated on an interface, it generates a local hotspot that induces convection currents, which assist in the aggregation of microparticles. This confinement technique facilitates the creation and manipulation of assemblies of nano- and microcolloidal particles and is thus employed in analyzing the characteristics of various interfacial systems, like liquid–solid, liquid–liquid, and air–liquid . The properties of such assemblies are vastly different from their constituent particles, because of which the phenomena can alter the interfacial properties in different systems …”
Section: Introductionmentioning
confidence: 99%
“…16−20 This confinement technique facilitates the creation and manipulation of assemblies of nano-and microcolloidal particles 21−23 and is thus employed in analyzing the characteristics of various interfacial systems, like liquid−solid, 22 liquid−liquid, 24−26 and air−liquid. 17 The properties of such assemblies are vastly different from their constituent particles, because of which the phenomena can alter the interfacial properties in different systems. 27 Colloidal particle assemblies can be induced by various phenomena, such as the fluid flow generated by thermal, 28 concentration, 29 and surface tension gradients, 30 which cause Marangoni convection, 17 thermal convection, 31 and thermophoresis 32 resulting in particle migration and thus selfassembly.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is generally believed that the particles are trapped only in an irradiated diffraction limited spot where optical force is exerted on the particles by a laser beam. However, in recent years, it has been demonstrated that single beam optical tweezers can gather lots of colloidal particles outside the focus of trapping laser at the glass-solution interfaces [16][17][18][19][20][21][22]. The mechanism of the above phenomenon is complicated.…”
Section: Introductionmentioning
confidence: 99%